Video Game Copyright Against Piracy Action Under The Law Number 28 of 2014 - Subakti, Muhammad Ramzy (Faculty of Law, Universitas Airlangga, 2024)
With Indonesia becoming a more and more industrialized country, as one of the fast growing economy it has developed a mass consumerism conduct as one of the entertainment to meet consumerism needs Most people in Indonesia in the recent years have a trend for playing video games but most good games doesn't come with a free price and the newer game brand have a very expensive price for a third world country such as Indonesia, so people though for another option is to pirate the game from any online website that provides the necessity to pirate a software. Then what are the legal protection for the game developer to avoid this sort of action in Indonesia.